ANALISIS FAKTOR KUALITAS PELAYANAN PADA RUMAH MAKAN XYZ JAKARTA - Zainuddin, Zulkifli (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
This study aims to determine the influence of promotion and quality of service to customer satisfaction in Restaurant XYZ Jakarta. The population in this study is the visitors who visited the XYZ Tebet Restaurant period of December 17, 2017. Sampling will stop after the fulfillment of the time range for 5 days and obtained the number of samples of 35 respondents with convenience sampling method. The analysis test used in this research is factor analysis test. The results of this study indicate that the factors that are most able to explain the quality of service is a factor is the ability factor to help visitors. This factor consists of: (1) Physical facilities (3) Responsiveness, (4) Able to help (5) Friendly (6) Polite. The second factor is the waiter has a firm nature consisting of a firm attitude. Keywords: service quality